Understanding the Jastip Business Model Phenomenon in Indonesia - angraini, nadia; Yeni, Yulia Hendri; Yulihasri, Yulihasri; Syafrizal, Syafrizal (AMAR (Andalas Management Review), 2024)
"Jastip" business model is one of the new business phenomena in Indonesia whose development is increasing in demand every year. Jastip or known as a consignment service is one of the businesses carried out by someone who is traveling both abroad and domestically, then opens a service to buy goods that other people want. When a literature review is carried out, there are limitations in research that studies this phenomenon, some say that the jastip business is the same as a personal shopper, some say differently. In addition, various other names of this jastip business have emerged such as Entrusted service agent, Shopping entrusted goods service, Deposit Service, and Entrusted services. Thus, it is necessary to have a deeper review of this jastip business concept phenomenon. This study uses a qualitative approach method of literature review which summarizes the important points in previous research so that the actual concept or description of Jastip's business is found. The results of the study show that the jastip business is different from personal shoppers. The jastip business is only a representative service to buy goods ordered by consumers and get a fee outside of the product price, in contrast to personal shoppers whose profession must be professional in exploring product information. This research is expected to be one of the contributions for future researchers, especially those who study the phenomenon of the Jastip.